2021
DOI: 10.23960/jep.v10i3.280
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Pengangguran Terdidik Lulusan Universitas di Pulau Jawa

Abstract: This study aims to determine the factors that influence educated unemployment in Java. The data used in this study is secondary data using quantitative methods. Data analysis uses panel data analysis which is a combination of time series and cross-section data. The time-series data uses data for the 2015-2019 period and cross-section data from 6 provinces on the island of Java. The results showed that simultaneously all variables had a significant effect on the level of educated unemployment. While partially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Within this intricate ecosystem of labor market dynamics lies the phenomenon of educated unemployment, wherein individuals with advanced education levels face joblessness despite their qualifications (Anjarwati & Juliprijanto, 2021). Rooted in a myriad of factors, including labor market imbalances, closed recruitment networks, perceived deficiencies in university education, and mismatched employment expectations, educated unemployment poses a significant challenge.…”
Section: Concept Of Educated Unemploymentmentioning
confidence: 99%
“…Within this intricate ecosystem of labor market dynamics lies the phenomenon of educated unemployment, wherein individuals with advanced education levels face joblessness despite their qualifications (Anjarwati & Juliprijanto, 2021). Rooted in a myriad of factors, including labor market imbalances, closed recruitment networks, perceived deficiencies in university education, and mismatched employment expectations, educated unemployment poses a significant challenge.…”
Section: Concept Of Educated Unemploymentmentioning
confidence: 99%
“…Another factor that affects the number of educated unemployed people is the minimum wage, which is said to be inversely proportional to the local unemployment rate. Additionally, research by Anjarwati and Juliprijanto (2021) revealed that wages have an effect on the educated unemployment rate. This is in agreement with the labor demand theory.…”
Section: Image I11 the Number Of Educated Unemployed Individuals In J...mentioning
confidence: 99%
“…Hal ini sejalan dengan pendapat yang menerangkan bahwa pengangguran lulusan perguruan tinggi mencapai angka 6,75% ini disebabkan karena lulusan pendidikan tinggi meningkat setiap tahunnya selain itu juga karena sempitnya lapangan pekerjaan, ketimpangan jurusan dengan yang dibutuhkan dalam perusahaan, hingga kualitas lulusan yang kurang bermutu (Gusdwisari, 2020). Pendapat lain menyatakan bahwa tingginya pengangguran pada tingkat lulusan terdidik disebabkan karena tingkat pendidikan yang dibutuhkan oleh perusahaan, upah minimum tiap daerah, dan ekspektasi yang terlalu tinggi (Anjarwati & Juliprijanto, 2021). Oleh sebab itu dibutuhkan mutu lulusan yang tinggi untuk menepis segala faktor-faktor penyebab melonjaknya pengangguran dan fokus mempelajari strategi untuk dapat menembus pasar industri atau bisa juga memberikan keterampilan agar mereka secara mandiri bukan sebagai pekerja melainkan sebagai pencipta pekerjaan.…”
Section: Pendahuluanunclassified